The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3389/fimmu.2019.02936
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoints in Circulating and Tumor-Infiltrating CD4+ T Cell Subsets in Colorectal Cancer Patients

Abstract: Blockade of inhibitory immune checkpoints (ICs) is a promising therapeutic approach; however, it has shown limited success in some cancers including colorectal cancer (CRC). The tumor microenvironment (TME) is largely responsible for response to therapy, and its constituents may provide robust biomarkers for successful immunotherapeutic approaches. In this study, we performed phenotypical characterization and critical analyses of key inhibitory ICs and T regulatory cell (Treg)-related markers on CD4 + T cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
102
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 67 publications
5
102
0
1
Order By: Relevance
“…21 We have previously reported that CD4 + T cell infiltration was significantly higher in the CRC microenvironment, compared with normal tissue with no significant differences between early and advanced stages. 12 In this study, we investigated the transcriptomes and potential functional networks of CD4 + TILs from various stages of CRC. Our analyses led to developing a gene signature based on the transcriptome of CD4 + TILs with a prognostic potential for CRC.…”
Section: Discussionmentioning
confidence: 99%
“…21 We have previously reported that CD4 + T cell infiltration was significantly higher in the CRC microenvironment, compared with normal tissue with no significant differences between early and advanced stages. 12 In this study, we investigated the transcriptomes and potential functional networks of CD4 + TILs from various stages of CRC. Our analyses led to developing a gene signature based on the transcriptome of CD4 + TILs with a prognostic potential for CRC.…”
Section: Discussionmentioning
confidence: 99%
“…10 Similarly, an elevated percentage of CD3 + and CD8 + T cells in colorectal cancer was found to be related to improved OS, whereas a decreased percentage of T-cells was associated with poor prognosis. 41 As shown by Darb-Esfahani and colleagues, the presence of different subpopulations of TILs, including CD4 + and CD8 + T cells, is related to a better prognosis for OC patients. 32 Similar findings have been reported by Webb and co-workers.…”
Section: Discussionmentioning
confidence: 95%
“…All patients provided written informed consent prior to sample collection. Peripheral blood mononuclear cells (PBMCs) were isolated from fresh blood using Histopaque gradient centrifugation and stored, as previously described ( 17 ). This study was performed under ethics approvals from Hamad Medical Corporation, Doha, Qatar (protocol no.…”
Section: Methodsmentioning
confidence: 99%
“…Isolated PBMCs were stained as previously described ( 17 , 18 ). Briefly, cells were stained with antibodies against CD33–fluorescein isothiocyanate (clone HIM3-4; BD Biosciences, Oxford, UK), HLA DR–phycoerythrin (clone G46-6; BD Biosciences), CD14–phycoerythrin–Cy7 (clone M5E2; BD Biosciences), and CD15–allophycocyanin (clone HI98; BioLegend, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation